The Effect of The L/G Ratio on SO2 Removal Efficiency in Seawater Absorption Columns - Kadek, Sri Anik Suci; Dewi, Kania (Journal of Community Based Environmental Engineering and Management, 2023)
Steam Turbine Power Plants are widely known as one of the primary sources of electricity generation, utilizing coal combustion. However, this process leads to the emission of air pollutants, including sulfur dioxide (SO2), which is considered harmful. To mitigate this issue, Seawater Flue Gas Desulfurization (SWFGD) has been implemented as a control device to reduce the concentration of SO2. Previous studies on SWFGD have mainly focused on operational factors such as gas flow rate and liquid flow rate using artificial seawater as the absorbent. However, there is a lack of research on utilizing natural seawater, particularly from Indonesia, as the absorbent. Hence, this study aims to determine the efficiency of SO2 removal using Indonesia's natural seawater and investigate the influence of varying the L/G (liquid-to-gas) ratio on the overall removal efficiency. The study employed a packed tower reactor with a counter-current flow configuration. The gas concentration of SO2 used in this study is 1500 ppm, which is adjusted to match the existing conditions in the Steam Turbine Power Plant. The variations in seawater flow rate range from 150 to 250 liters/hour, while the variations in gas flow rate range from 1 to 10 m3/hour at 30oC. So, the L/G ratio value is within the range of 20.9 to 104.5. The results indicated that an increase in the L/G ratio corresponded to an increase in the total removal efficiency. The highest achieved efficiency reached 98.5%, while the lowest efficiency recorded was 84%.